Preparation and characterization of decorative and heat insulating floor tiles for buildings roofs - Ashraf, Basant; A. Radwan, Mostafa; A. Sadek, M.; A. Elazab, Hany (International Journal of Engineering and Technology, 2018)
Since the beginning of the 5th century, people felt the urge to construct a sort of heat insulation system to their houses. This research paper focuses on the preparation, development and design of heat insulating tiles using materials like automobile tires powder and rice husk which are materials that are available at almost negligible costs and great amounts. Throughout this paper, experimental work will be provided to document, analyze and compare different insulating materials based on their thermal conductivity factor (K-factor), economic aspects, contribution to a greener earth, and mechanical properties. The results show that a mixture of used automobile tires powder and epoxy has a K factor of 0.0117 W/m°C, and that of a rice husk mixture with epoxy is 0.0118 W/m°C. These values are considerably lower than the K factor of the currently used polyurethane foam (which is 0.026 W/m°C), and therefore these mixtures are more efficient heat insulators than the currently used foam. Calculations have also shown that the manufacture of these mixtures cost 65% less than that of the polyurethane foam.